Rol de la alteración del eje microbiota-intestino-hígado en la enfermedad hepática esteatósica asociada a disfunción metabólica - Ortiz-López, Nicolás; Acevedo, Maximiliano; Vergara, Tamara; Aleman F., Larissa; Poniachik T., Jaime; Beltran M., Caroll J. (Revista Hospital Clínico Universidad de Chile, 2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is one of the leading causes of liver morbidity worldwide, including conditions such as hepatocellular carcinoma and the need for liver transplantation, with a particularly high prevalence in Latin America. The pathogenesis of MASLD is multifactorial, involving both genetic and environmental factors, including dysfunction of the gut-liver axis. The mechanisms involved in the progression of liver disease to cirrhosis are not yet fully understood. Recently, the intestinal microbiota has been recognized as playing a crucial role in disease progression by modulating systemic and hepatic inflammatory responses. In MASLD patients, microbial dysbiosis contributes to intestinal barrier dysfunction, increasing intestinal permeability and facilitating the translocation of microbial products to the liver, thereby exacerbating inflammation and hepatic damage. Additionally, alterations in bile acid levels and microbial metabolites further reinforce this pathological cycle. Therapeutic strategies aimed at restoring microbial balance—such as fecal microbiota transplantation, probiotics, prebiotics, and synbiotics—have shown promising results in modulating the microbiota-gut-liver axis and slowing MASLD progression. Further studies are needed to fully understand their impact on the pathophysiology of MASLD and to strengthen their integration into current therapeutic protocols for this disease.